2009
DOI: 10.1073/pnas.0907173106
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis lipins mediate eukaryotic pathway of lipid metabolism and cope critically with phosphate starvation

Abstract: Phosphate is an essential nutrient for plant viability. It is well-established that phosphate starvation triggers membrane lipid remodeling, a process that converts significant portion of phospholipids to non-phosphorus-containing galactolipids. This remodeling is mediated by either phospholipase C (PLC) or phospholipase D (PLD) in combination with phosphatidate phosphatase (PAP). Two PLC genes, NPC4 and NPC5, and PLD genes, PLD1 and PLD2, are shown to be involved in the remodeling. However, gene knockout stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
250
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(259 citation statements)
references
References 45 publications
9
250
0
Order By: Relevance
“…Two homologous genes designated PAH1 and PAH2 have been identified in Arabidopsis (54 -56). Loss of function of PAH1 and PAH2 in Arabidopsis disrupted membrane remodeling, suggesting a role in the eukaryotic pathway of DAG formation (54). Furthermore, pah1/pah2 double mutants showed increased PC and overall expansion of the ER in leaves, consistent with a function in regulating membrane phospholipid accumulation as in animals and yeast (55), although the mechanism(s) remain to be elucidated.…”
Section: Conventional Kennedy Pathwaymentioning
confidence: 86%
“…Two homologous genes designated PAH1 and PAH2 have been identified in Arabidopsis (54 -56). Loss of function of PAH1 and PAH2 in Arabidopsis disrupted membrane remodeling, suggesting a role in the eukaryotic pathway of DAG formation (54). Furthermore, pah1/pah2 double mutants showed increased PC and overall expansion of the ER in leaves, consistent with a function in regulating membrane phospholipid accumulation as in animals and yeast (55), although the mechanism(s) remain to be elucidated.…”
Section: Conventional Kennedy Pathwaymentioning
confidence: 86%
“…To verify if altered levels of PCho and PEth could lead to the transcriptomic activation or inhibition of specific lipid metabolism pathways, we selected several genes representative of membrane lipid recycling pathways triggered during Pi starvation (Nakamura, 2013). These genes included NPC4 (representative of the nonspecific PLC pathway; Nakamura et al, 2005), PLDz1 and 2, PAH1 and 2 (for the PLD/PAP pathway; Qin and Wang, 2002;Li et al, 2006;Nakamura et al, 2009;Eastmond et al, 2010), and GDPD1, 2, 3, 5, and 6 (for the LAH/GDPD pathway; Cheng et al, 2011). In response to a lack of Pi, we observed that NPC4, PLDz2, and GDPD1, 2, 3, 5, and 6 were induced in wild-type plants as previously reported (Supplemental Fig.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedmentioning
confidence: 99%
“…The Arabidopsis genome harbors two highly similar lipin homolog genes encoding Mg 2+ -dependent PAHs that function redundantly in catalyzing the dephosphorylation of phosphatidic acid (PA) to DAG (Nakamura et al, 2009;Eastmond et al, 2010), the direct precursor of TAG and phospholipids. To test their role in TAG synthesis and FA degradation in leaves, we constructed a double mutant lacking PAH1 and PAH2 by genetic crossing.…”
Section: Pah1 and Pah2 Are Required For Tag Synthesis In Leavesmentioning
confidence: 99%